2010
DOI: 10.1259/dmfr/82724776
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two-dimensional radiography and three-dimensional computed tomography in angular cephalometric measurements

Abstract: Objectives: The objective of this study was to assess the reliability of three-dimensional (3D) cephalometric approaches by comparing this method with authenticated traditional twodimensional (2D) cephalometry in angular cephalometric measurements. Methods: CT images and lateral cephalometric radiographs of ten patients (five women, five men) were used in this study. Raw CT data of the patients were converted to 3D images with a 3D simulation program (Mimics 9.0, Leuven, Belgium). Lateral cephalometric radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 25 publications
1
64
0
2
Order By: Relevance
“…As our results, they did not find statistically significant differences for either the Na-Me or Ans-Me distances, concluding that it is possible to use most of the values previously established in 2D for measuring 3D records, as the differences between both systems were small. Other authors have also compared angular measurements between LCR and CT. 30 They found only statistically significant differences in 2 of the 14 measurement that they carried out, upper incisor-Na and upper incisor-NS. However, in our study, we did not find such difference for the upper incisor-NS angle.…”
Section: Discussionmentioning
confidence: 90%
“…As our results, they did not find statistically significant differences for either the Na-Me or Ans-Me distances, concluding that it is possible to use most of the values previously established in 2D for measuring 3D records, as the differences between both systems were small. Other authors have also compared angular measurements between LCR and CT. 30 They found only statistically significant differences in 2 of the 14 measurement that they carried out, upper incisor-Na and upper incisor-NS. However, in our study, we did not find such difference for the upper incisor-NS angle.…”
Section: Discussionmentioning
confidence: 90%
“…[5,10,27,31À33] However, few studies have used CBCT-generated cephalograms using rendering programs in vivo. [5,6,14,27,34] The current study evaluated the reliability of linear and angular measurements in four rendering software programs; either in 2D or 3D generated cephalograms. According to the results, most of the cephalometric parameters used in this study showed no statistical differences between the measurements obtained by 2D Vista Dent tracing method and those obtained from CBCT-generated cephalograms (p > 0.05).…”
Section: Intra-observer Reproducibilitymentioning
confidence: 99%
“…Nalcaci et al [6] evaluated 3D cephalometric images and traditional 2D images in terms of angular measurements. They also used a third-party software program (Mimics 9.0, Leuven, Belgium).…”
Section: Intra-observer Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral cephalometric radiography (LCR) has been used since 1931 1 as a standard tool for craniofacial morphology analysis, orthodontic diagnosis, and treatment. [2][3][4] Using LCR, longitudinal studies of craniofacial growth and development were performed for analysis of dentoskeletal relationships in individuals with normal facial pattern. From these studies, standard measures of craniofacial relationships were obtained.…”
Section: Introductionmentioning
confidence: 99%